2009
DOI: 10.3892/ijo_00000322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IFN-β on human glioma cell lines with temozolomide resistance

Abstract: Abstract. Human interferon-ß (IFN-ß) is known to exhibit pleiotropic biological activities including antitumor effects. On the other hand, temozolomide (TMZ), an oral bioavailable alkylating agent with excellent tolerability, has demonstrated efficacy and has become a key therapeutic agent in patients with malignant gliomas; however, its survival benefit remains unsatisfactory. More recent studies have indicated that there might be favorable therapeutic interactions between IFN-ß and TMZ, although the therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Natsume et al suggested that a sensitizing effect between IFN-β and TMZ in TMZ-resistant glioma cells was possibly due to an attenuation of MGMT expression via induction of the protein p53 (10). Furthermore, we demonstrated that a significant synergistic antitumor effect and downregulated quantitative MGMT mRNA levels were observed when TMZ was combined with IFN-β at clinically relevant concentrations, as compared to treatment with TMZ or IFN-β alone in TMZ-resistant glioma cells, and that significant amounts of endogenous IFN-β protein were detected in the TMZ-treated cells by ELISA (12).…”
Section: Gene Expression Profiles Predicting the Response To Ifn-β Anmentioning
confidence: 68%
See 2 more Smart Citations
“…Natsume et al suggested that a sensitizing effect between IFN-β and TMZ in TMZ-resistant glioma cells was possibly due to an attenuation of MGMT expression via induction of the protein p53 (10). Furthermore, we demonstrated that a significant synergistic antitumor effect and downregulated quantitative MGMT mRNA levels were observed when TMZ was combined with IFN-β at clinically relevant concentrations, as compared to treatment with TMZ or IFN-β alone in TMZ-resistant glioma cells, and that significant amounts of endogenous IFN-β protein were detected in the TMZ-treated cells by ELISA (12).…”
Section: Gene Expression Profiles Predicting the Response To Ifn-β Anmentioning
confidence: 68%
“…Our prior studies have shown that T98G, U-138MG and YH-13 had MGMT mRNA and protein expression, whereas A-172, AM-38, U-87MG and U-251 did not have them (3). Further, a synergistic antitumor effect of combination treatment with IFN-β and TMZ was observed in the TMZ-resistant glioma cells, T98G, due possibly to an attenuation of their MGMT mRNA levels (12). However, in the present study, other MGMT-positive cell lines, at least YH-13, did not exhibit a synergistic effect between IFN-β and TMZ, whereas the MGMT-negative cell line, A-172, displayed a synergistic effect with a combination of TMZ and IFN-β.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Parts of the results obtained have recently been reported elsewhere (22,23) Table V. MGMT methylation status, quantitative of MGMT mRNA, and MGMT protein expression in seven malignant glioma cell lines.…”
Section: ------------------------------------------------------------mentioning
confidence: 91%
“…To determine the protein levels of MGMT, Western blot analysis was employed as described previously (22,23). Briefly, soluble protein lysates of glioma cells were obtained employing lysis buffer (Medical & Biological Laboratories, Woburn, MA, USA) for 20 min on ice.…”
Section: Methodsmentioning
confidence: 99%